Photonic Technologies for Millimeter- and Submillimeter-Wave Signals. (13th November 2012) - Vidal, B.; Nagatsuma, T.; Gomes, N. J.; Darcie, T. E.
Abstract : Fiber optic components offer a competitive implementation for applications exploiting the millimeter-wave and THz regimes due to their capability for implementing broadband, compact, and cost-effective systems. In this paper, an outline of the latest technology developments and applications of fiber-optic-based technologies for the generation, transmission, and processing of high-frequency radio signals is provided.